Change of configuration, morphology and roughness of metals being electrodeposited at the force influence - Гирин, Олег Борисович; Захаров, Игорь Демьянович (Eastern-European Journal of Enterprise Technologies, 2014)
The aim of the work was experimental verification of validity of the phenomenon of phase formation through a stage of liquid state in metals being electrodeposited. The idea of the work was based on the known fact that the main difference between solid and liquid states of metal is the value of fluidity. Therefore, if phase formation of metal during electrodeposition passes a stage of liquid state than changes of configuration, morphology and roughness of its surface at the external force influence parallel to the crystallization front should be expected. Configuration of the formed deposit should have anisotropic form elongated in the direction of the force influence. Surface morphology of such deposit should be smoother and its surface should have lesser roughness in comparison with the deposit electrodeposited in usual conditions. To realize the idea of the work the electrochemical cell for obtaining of metals being electrodeposited at the external force influence in conditions of restrained deposit formation was developed and constructed. On the basis of model experiments the effects of formation of anisotropic configuration of the deposit of metal being electrodeposited, smoothing of morphology and decrease of roughness of its surface under the influence of the external force directed parallel to the crystallization front were established. The obtained result proves the validity of the phenomenon of phase formation through a stage of liquid state in metals being electrodeposited.